Biopharmaceutical Trials of a Dosage Form, which Contain Methionine and Turmeric Extract (Curcuma longa L.) - O. A. Gizinger; A. A. Khisamova (Разработка и регистрация лекарственных средств, 2021)
Introduction. The presence of biologically active substances in the extract from the roots of turmeric extract (Curcuma longa L.) makes it reasonable and makes it possible to predict their effectiveness in pathological conditions caused by oxidative stress and immune disorders arising against its background. Based on data obtained, a pattern was revealed in improving the solubility of the combination of methionine and turmeric extract, which includes auxiliary substances. Dosage form – granules with methionine and liquid turmeric extract, with enteric coat can be used to eliminate the consequences of oxidative and immune disorders, treatment and prevention of systemic diseases caused by oxidative stress.Aim. Biopharmaceutical and in-process tests of the pharmaceutical composition of granules with methionine and liquid turmeric extract.Materials and methods. The object of the trials was the multicomponent drug containing methionine and a liquid turmeric extract of the roots. The proposed composition of plant compositions is original, had no analogues and protected by a patent for an invention (RU 268 4111). To assess the pharmaceutical properties, biopharmaceutical trials carried out by the UV-spectrophotometric method using biorelevant medium. The research results statistically processed using Statistica for Windows, version 10.Results and discussion. Based on the data obtained, a pattern revealed in improving the solubility of the combination of methionine and turmeric extract, in contrast to the multicomponent composition containing only turmeric extract.Conclusion. The developed multicomponent pharmaceutical composition will expand the register of herbal medicines of domestic production for the prevention and treatment of diseases caused by oxidative stress.